DEVELOPMENT OF THE INTELLECTUAL PROPERTY INSURANCE SYSTEM IN TRANSPORT TECHNOLOGIES: PERSPECTIVES AND CHALLENGES - Novalska , N. I.; Derevianchuk К. M.; Lozovyi , D. O.; Yeroshenko , O. R. (The actual problems of regional economy development, 2024)
The article explores the strategic importance of intellectual property (IP) insurance within the rapidly evolving technological and digital landscape. By emphasizing the novelty of applying IP rights insurance for Ukrainian enterprises and the insurance companies themselves, the authors examine the prerequisites for the emergence and development of IP rights insurance in Ukraine. The research was conducted through a detailed study and analysis of the operational experience of transport and logistics companies. The paper underscores the critical role of IP protection in transport technologies, which is essential for ensuring the competitiveness and innovative development of companies. The authors analyze the specific situations in which transport enterprises should implement IP insurance. They highlight that, especially during wartime, companies face substantial risks of loss due to destruction, theft, or cyber-attacks on their intellectual assets. To manage these risks and mitigate potential losses, insuring intellectual assets is recommended. The authors explore various scenarios where transport company owners can utilize this contemporary business tool effectively. Additionally, the article presents an analysis of the global patent landscape within the transport sector, which provides valuable insights into current trends and developments. The growing demand for IP insurance services in Ukraine reflects the increasing awareness among business owners and top managers regarding the importance of protecting innovations and managing associated risks. The article also discusses trends and modern tendencies in the creation of new insurance products and the expansion of coverage for losses related to the infringement or loss of IP rights. This demonstrates the continuous adaptation of insurance companies to the evolving technological environment. Furthermore, the study identifies the challenges faced by insurance companies in the IP market, emphasizing the necessity for ongoing research to address these challenges. Such research is crucial for ensuring effective protection and fostering the development of innovations on a global scale. The authors conclude that the strategic implementation of IP insurance can significantly contribute to the sustainability and resilience of companies, particularly in high-risk environments. This, in turn, supports broader economic stability and growth by safeguarding the intangible assets that drive innovation and competitive advantage. The need for further scientific exploration and development of specialized insurance products tailored to the unique risks associated with IP underscores the importance of this field in the contemporary business landscape.